Testosterone Induces Relaxation of Human Corpus Cavernosum Tissue of Patients With Erectile Dysfunction. Issue 1 (22nd November 2019) - Van den Broeck, Thomas; Soebadi, Mohammad Ayodhia; Falter, Annelies; Raets, Lore; Duponselle, Jolien; Lootsma, Joline; Heintz, Alexander; Philtjens, Uchelly; Hofkens, Lien; Gonzalez-Viedma, Arantxa; Driesen, Karel; Sandner, Peter; et al.
Abstract: Introduction: Previous research in the field of cardiovascular diseases suggests a relaxing effect of testosterone (T) on smooth muscle cells. Therefore, it was hypothesized that T could play a significant role in erection development. Aim: To investigate the relaxing effect of T and other molecules of the T signaling pathway on human corpus cavernosum (HCC) tissue. Methods: Samples of the HCC tissue were obtained from men who underwent penile prosthesis implantation (n = 33) for erectile dysfunction. Samples were used for isometric tension measurement in Ex Vivo experiments. Following standardized precontraction with phenylephrine, increasing doses of T or dihydrotestosterone were administered and blocked by NO/H2 S synthesis inhibitors, a KATP blocker, and flutamide (androgen receptor inhibitor). Main Outcome Measure: The outcome was relaxation of the HCC tissue, normalized to a maximum precontraction achieved by phenylephrine. Results: A dose-dependent relaxing effect of dihydrotestosterone and T was observed with a relaxation of, respectively, 24.9% ± 23.4% ( P < .0001) and 41.7% ± 19.1% ( P = .01) compared with 6.8% ± 15.9% for vehicle (dimethylsulfoxide) at 300 μM. The relaxing effect of T was not countered by blocking NO synthesis, H2 S synthesis, KATP channels, or the androgen receptor. Clinical Implications: By understanding the underlying mechanisms of T-induced HCC relaxation, potential new therapeutic targets can be identified. Strengths & Limitations: The strength of the study is the use of fresh HCC tissues with reproducible results. The limitation is the need for supraphysiological T levels to induce the observed effect. Conclusion: Rapid androgen-induced relaxation of HCC is likely to occur via nongenomic mechanisms. Previously suggested mechanisms of action by which T modulates HCC relaxation have been excluded.